Management System in the Almohad State | نظام الإدارة في الدولة الموحدية - Aminah Iraqi (Al-Zahra : Journal for Islamic and Arabic Studies, 2017)
The Almohad state witnessed a great civilizational prosperity in differentpolicitical, economic and administrative fields. This state was established on thebasis of a reformist religious claim characterized with renewing aiming forachieving a comprehensive Islamic unity. That unity was started by Mehdi IbnTumart in 515 AH/ 1121 A.C and established by Abd al-Mu'min Ibn Ali in 524AH/ 1129 AC through submitting Maghreb and Andalus at his disposal. Thisregion The most important civilizational prosperity were the mandate ofcovenant, the ministry, janitorial functions, and all different kinds ofadministrative divans ( دواوين ) in addition to the judiciary, grievances divan,accountancy, police, public control, police, army and naval fleet.